Investigation into the ability of pervious pavement to treat stormwater for aquifer storage and recovery - Taylor, Christopher John (Curtin University, 2013)
Pervious pavement is investigated as a tool to treat stormwater for Aquifer Storage and Recovery (ASR). Adding a layer of Granular Activated Carbon (GAC) and adding a sand layer to the base were investigated separately. Both arrangements were shown to be capable of reducing ammonium to meet ASR requirements, with the sand layer setup also meeting phosphate requirements. Suspended solids and oxidised nitrogen were more problematic and should be the focus of further research.